Fatty Acid Composition, Cholesterol and Nutritional Indices of Srinidhi and Vanaraja Chicken Varieties at 16, 20 and 24 Weeks of Age - Katekhaye, Anita; Kumar, M. Shashi; Reddy, K. Kondal; Rao , Kessava (Journal of Meat Science, 2018)
The fatty acid profile and cholesterol content were studied in Srinidhi and Vanaraja chicken varieties – slaughtered at the 16, 20 and 24  weeks. All fatty acids studied were significantly (P
Keywords: Srinidhi; Vanaraja; Fatty acid profile; Cholesterol